Abdulla Avlani – Is the Founder of Uzbek Pedagogy - Juraev Oybek Sheralievich (Genius Publishing Group, 2023)
This article talks about the great representative of the Uzbek literature of the national renaissance period, one of the founders of the Jadid movement, the well-known pedagogue and statesman Abdulla Avlani, about his efforts in journalism, education, pedagogy, politics and the education of young people in the country
Keywords: Abdulla Avlani; jadidism; press; pedagogy; education; politics; drama